Strategi Pemasaran Produk Tabungan iB Siaga Bisnis PT. Bank KB Bukopin Syariah Kantor Cabang Medan dalam Meningkatkan Jumlah Nasabah - Batubara, Nur Azizah (CV. Kalimasada Group, 2023)
This research is intended to find out about the marketing strategy of iB Siaga Bisnis Savings products of PT. Bank KB Bukopin Syariah Medan Branch Office in Increasing the Number of Customers. This type of research is descriptive qualitative, using primary data sources by means of interviews, documentation, and observations which are then reduced and conclusions drawn. The results of research with STP, namely market segmentation divides into 2 parts, the first, assigning marketing to seek funds in terms of finding saving customers and the second looking for customers to make financing or loans. Targeting Bank Bukopin Syariah KC Medan markets its products among small and medium business entities and cooperatives (UKMK), legal entities such as associations, associations, individuals both entrepreneurs and employees (middle class), etc., and the market positioning of Bank KB Bukopin Syariah KC Medan uses marketing 4P mix, products that tempt customers, prices according to regulations and systems, strategic places and promotions using print media, online and personal selling. SWOT analysis of marketing strategy to provide alternative strategies to improve the marketing strategy of Bank KB Bukopin Syariah KC Medan. The SO strategy to improve harmonization that has been established is to collaborate with educational institutions. WO strategy to open a branch or cash office, increase the amount of marketing. ST strategy, determining competitive prices, WT strategy to improve the quality of human resources, limited service.